Visible‐Light Photocatalytic and Photo‐bactericidal Activity of Ni‐CuWO4/OTiO2 Composite†. Issue 22 (11th September 2022) - Meng, Shuangyan; Li, Li; Xi, Hui; Yang, Jing; Xiao, Ting; Zuo, Rui; Xu, Xueqing; Lei, Ziqiang; Yang, Zhiwang; Xue, Qunji
Abstract : Comprehensive Summary A series of nickel‐doped copper tungstate/oxygen‐rich TiO2 heterojunction‐constructed composites of x Ni‐CuWO4 /OTiO2 were successfully prepared to demonstrate the enhancement of the visible‐light photoactivity through promoting the photogenerated charge carrier separation efficiency. Of all these composites, 0.2Ni‐CuWO4 /OTiO2 exhibits excellent and stable visible light photoactivity for the photooxidative coupling of benzylamine to the corresponding N ‐benzyl‐1‐phenymethanimine (BPMI) in air atmosphere. The conversion of benzylamine and the selectivity to BPMI reach 97% and 99%, respectively. The catalyst shows good cyclability with the conversion of benzylamine decreasing just by 22% after being repeated six times with the well‐maintained selectivity of BPMI. The composite also exhibits excellent photo‐bactericidal ability, which greatly inhibits the reproducing of both the Gram‐positive bacteria ( e.g ., S. epidermidis ) and Gram‐negative bacteria ( e.g ., E. coli ). Abstract : Ni 2+ may easily replace Cu 2+ in CuWO4 crystal thereby improving its photocatalytic activity, and oxygen‐rich TiO2 can shorten the band gap structure of TiO2, which is beneficial to absorb visible light. Nickel‐doped copper tungstate/oxygen‐rich TiO2 Z‐scheme heterojunction‐constructed composites of x Ni‐CuWO4 /OTiO2 were successfully synthesized to demonstrate the enhancement of the visible‐light photoactivity through promoting the photogenerated charge carrier separation efficiency.